Pengaruh frekuensi pemupukan setelah forcing terhadap produktivitas buah tanaman nanas (Ananas comosis [L.] Merr.) - Azizah, Nur; Widyastuti, R. A. Diana; Karyanto, Agus; Ginting, Yohannes Cahya (JURNAL AGROTROPIKA, 2023)
Pineapple (Ananas comosus [L.] Merr) is one of the potential horticultural commodities and is a mainstay of exports in Indonesia.  Pineapple fruit productivity can be increased through the fertilization process. One of the fertilization processes in pineapple plants is fertilization after forcing.  The nutrients needed by pineapple plants after forcing are nitrogen and potassium which can support plant growth and increase pineapple fruit production. The purpose of this study was to determine the effect of the frequency of fertilization after forcing and to find out which treatment had the highest productivity. The research was conducted from October 2022 to April 2023 at the Central Lampung Pineapple Plantation, Lampung Province. This study used a single factor randomized block design (RBD), namely the frequency of fertilization on the day after forcing (HSF). The treatment consisted of four levels, namely twice fertilization given at 20 and 55 HSF (P1), two times fertilization given at 15 and 30 HSF (P2), three times fertilization given at 15, 30, 45 HSF (P3) and four times of fertilization given at 15, 30, 45, 60 HSF (P4). Each fertilization application uses Urea 50 kg/ha and K2SO4 75 kg/ha. Each treatment was repeated four times to obtain 16 experimental units. The results showed that the frequency of fertilization after forcing had an effect on the weight of 12 eyed fruit, the length of 11 and 12 eyed fruit, the diameter of 12 eyed fruit, and the weight of 12 eyed crowns in pineapple plants. The fertilization that was able to produce the best pineapple fruit productivity was fertilization with twice the frequency at 15 HSF and 30 HSF which produced the highest production potential compared to the control treatment with a difference of 2.51%.Keywords : pineapple, fertilization, HSF (Days After Forcing)